AMG900 as novel inhibitor of the translationally controlled tumor protein. (25th January 2021) - Fischer, Nicolas; Seo, Ean-Jeong; Klinger, Anette; Fleischer, Edmond; Efferth, Thomas
Abstract: Introduction: Cancer is one of the leading causes of death worldwide. Classical cytotoxic chemotherapy exerts high side effects and low tumor selectivity. Translationally controlled tumor protein (TCTP) is a target for differentiation therapy, a promising, new therapeutic approach, which is expected to be more selective and less toxic than cytotoxic chemotherapy. The aim of the present investigation was to identify novel TCTP inhibitors. Methods: We performed in silico screening and molecular docking using a chemical library of more than 31, 000 compounds to identify a novel inhibitor of TCTP. We tested AMG900 in vitro for binding to TCTP by microscale thermophoresis and co-immunoprecipitation. Additionally, we examined the effect of TCTP blockade on cell cycle progression by flow cytometry and Western blotting and cancer cell survival by resazurin assays in MCF-7, SK-OV3 and MOLT-4 cell lines. Results: We identified AMG900 as new inhibitor of TCTP. AMG900 bound to the p53 binding site of TCTP with a free binding energy of −9.63 ± 0.01 kcal/mol. This compound decreased TCTP expression to 23.4 ± 1.59% and increased p53 expression to 194.29 ± 24.27%. Furthermore, AMG900 induced G0/G1 arrest as shown by flow cytometry and Western blot of relevant cell cycle proteins. AMG900 decreased CDK2, CDK4, CDK6, cyclin D1 and cyclin D3 expression, whereas p18, p21 and p27 expression increased. Moreover, AMG900 disturbed TCTP-p53 complexation as shown by co-immunoprecipitation and increased expression of free p53. Discussion: AMG900 may serve as novel lead compound for the development of differentiation therapy approaches against cancer.